Letter from Marianne Homburger to Georg and Max Bredig, January 16, 1941 - Homburger, Marianne (1941)
In a letter to her father, Georg Bredig (1868-1944), and brother, Max Bredig (1902-1977), Marianne Homburger (1903-1987) details her life in the Gurs concentration camp, including its dire circumstances and her hopes for the future. A note is included at the end of the letter from her husband, Viktor Homburger (1888-1968).
Keywords: Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Jewish Holocaust (1939-1945); Gurs (Concentration camp)